Discourse analysis of speech acts and instructional strategies employed during bedside teaching sessions in public sector hospitals in Iraq - Mohammad, Suzan Salih (2021)
Previous research has found that bedside teaching is an effective and commonly used teaching method in medical education. However, few studies have analysed the language and instructional strategies used during real-life interactions during bedside teaching sessions. Past research investigated the effectiveness of bedside teaching methods from medical instructors’ and students’ perspectives and the influences of the relationships between instructors and students on the success of this teaching method. This study attempted to fill the gap in the literature mentioned above by shedding more light on the discourse of bedside teaching in Iraqi hospitals from a linguistic perspective. The focus of the study was on conducting discourse analysis to investigate the use of a number of speech acts and instructional strategies and their roles in enabling students’ understanding, improving the transfer of knowledge to students, and facilitating the organisation of students’ activities. The data were collected qualitatively in the form of 26 video recordings of 13 medical instructors and 48 medical students in interactions in two public hospitals in the Kurdistan region of Iraq during bedside teaching sessions. The recordings were transcribed, coded, and analysed using a mixed-mode technique. Speech act theory and various analytical frameworks such as those of Todd (1983), Nilsson et al. (2010), and Ramsden (2003) were included in the theoretical framework of the study. The findings revealed that five types of speech acts, namely, questions, reactives, statements, directives, and answers, were the most frequently performed by the instructors. This reflected the instructor-centred nature of bedside teaching sessions in Iraq’s Kurdistan region. The findings also revealed that these types of speech acts achieved various pragmatic functions. Furthermore, findings revealed that seven instructional strategies associated with various pragmatic functions were employed by the instructors, including questions and answers, piloting, prompting, supplementing, lecturing, intervening, and demonstrating. The question and answer strategy was the most frequently used followed by the piloting and prompting strategies. Moreover, the current research concluded that these actions play essential roles in promoting students’ understanding and knowledge, motivating them to participate in medical discussions, and helping them to focus more on the diagnosis and treatment of the patients. These findings imply that the use of proper speech acts and effective instructional strategies that suit communicative medical events would have an impact on the understanding, expectations, and situational needs of medical students. These findings have many pedagogical implications relevant to the fields of medical education and applied linguistics. For instance, the knowledge of various types of speech acts and instructional strategies would assist medical instructors to carry out more effective bedside teaching sessions. Despite the limitations, this study represents a pioneering attempt to analyse bedside teaching sessions in an Iraqi context. It could therefore form a basis and starting point for future research in the fields of medical education and applied linguistics.